Feasibility of implementing a preventive physical exercise programme recommended by general practitioners in cardiovascular risk patients: A pre-post comparison study - López-Román, Francisco Javier; Tornel-Miñarro, Francisca I.; Delsors-Merida-Nicolich, Eloisa; Fernández-López, Lourdes; Martínez-Ros, María Teresa; García Sánchez, Esther; López-Santiago, Asensio (The European journal of general practice, 2020)
Physical inactivity implies a significant individual and society health burden. To assess the feasibility of implementing a preventive physical exercise (PE) programme for the general population and to analyse changes in fitness-related variables and quality of life. Pre-post comparison study in which general practitioners and nurses recommended PE to participants with sedentary behaviour and hypertension or dyslipidaemia attending in primary care for primary prevention of ischaemic cardiovascular disease. Eligible participants were referred to a PE programme (10 weeks, three days a week, a total of 30 sessions of one-hour duration). Data was collected for five years (2013-2017). Outcome measures were body weight, body mass index (BMI), physical condition (aerobic fitness, muscle strength, flexibility, balance), and quality of life (SF-36). The PE programme was offered to 6,140 eligible subjects; 5,077 (82.7%) accepted to participate and received a recommendation; 3,656 (69.6% women) started the programme and 2,962 subjects (80.9% women) finished the programme. After 10 weeks, there were significant improvements (mean difference, 95% CI) in aerobic fitness (2.55 ml/min/kg, 2.32-2.79), muscle strength (0.62 m, 0.57 to 0.67), flexibility (2.34 cm, 2.06 to 2.63) and balance (−0.46 falls, −0.60 to −0.33) as well as significant decreases in body weight (−0.41 kg, −0.64 to −0.17) and BMI (−0.27 kg/m 2 , −0.34 to −0.20). Implementation of a government-supported PE programme for the general population recruited in the primary care setting and recommended by healthcare professionals is feasible, and was associated with health benefits, mainly improvements in physical fitness.